ANALYSIS OF BANK FINANCIAL RATIOS IN CONVENTIONAL COMMERCIAL BANK AND ISLAMIC COMMERCIAL BANK - Saputri, Kiki Intan; Gursida, Hari; Herdiyana, Herdiyana (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2023)
ABSTRACTThis research aims to determine the differences in the financial performance of conventional commercial banks and Sharia commercial banks by using 5 bank financial ratios, namely Loan to loan-to-deposit ratio (LDR), Non-Performing Loan (NPL), Return on Assets (ROA), Return on Equity (ROE), Operating Expenses to Operating Income (BOPO) and Capital Adequacy Ratio (CAR). This research method is descriptive and comparative. The population taken for this research was 74 conventional commercial banks and 12 sharia commercial banks. Samples were taken using nonprobability sampling with a purposive sampling approach. The research results show that there are significant differences between conventional commercial banks and sharia commercial banks when viewed from ROA, ROE, and BOPO. Meanwhile, if we look at LDR/FDR, NPL/NPF, and CAR, there are no significant differences between conventional commercial banks and Sharia commercial banks. This implies that Islamic banks should be able to maximize income from each product and also optimize their operational costs.ABSTRAKPenelitian ini bertujuan untuk mengetahui perbedaan kinerja keuangan bank umum konvensional dan bank umum syariah dengan menggunakan 5 rasio keuangan bank, yaitu Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), Return on Asset (ROA), Return on Equity (ROE), Beban Operasional terhadap Pendapatan Operasional (BOPO) dan Capital Adequacy Ratio (CAR). Metode penelitian ini adalah deskriptif dan komparatif. Populasi yang diambil untuk penelitian ini adalah 74 bank umum konvensional dan 12 bank umum syariah. Sampel diambil dengan menggunakan non probability sampling dengan pendekatan purvosive sampling. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan antara bank umum konvensional dan bank umum syariah jika dilihat dari ROA, ROE dan BOPO. Sedangkan jika dilihat dari LDR/FDR, NPL/NPF dan CAR tidak terdapat perbedaan yang signifikan antara bank umum kovensional dan bank umum syariah. Hal ini mengimplikasikan bank syariah sebaiknya dapat memaksimalkan pendapatan dari setiap produk dan juga mengoptimalkan biaya operasionalnya.